2018
DOI: 10.1177/1687814018799614
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and effective distance of gas–liquid two-phase swirling flow induced by vortex tools

Abstract: Based on the mechanistic model of the two-phase swirling annular flow behavior, a calculation method for the effective distance of vortex tool is obtained by taking Kelvin-Helmholtz instability into account. The rationality of the proposed method is validated by comparing the predicted liquid film thickness and pressure under non-swirling flow with the commonly used correlations. Then, the influences of gas-liquid ratio, helix angle, and hub diameter of vortex tool on the liquid film thickness, pressure drop, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The formula for calculating the optimal helical angle of vortex tools was established. Zhang [7] established a mechanistic model for the prediction of the swirling annular two-phase flow behavior downstream of the vortex tool, which has a guiding significance for the optimization design and field application of vortex tools.…”
Section: Introductionmentioning
confidence: 99%
“…The formula for calculating the optimal helical angle of vortex tools was established. Zhang [7] established a mechanistic model for the prediction of the swirling annular two-phase flow behavior downstream of the vortex tool, which has a guiding significance for the optimization design and field application of vortex tools.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the following should be noted. In a number of previous papers [20,21,22,23], it was shown that when calculating turbulent circulation-longitudinal fluid flows, good convergence with experimental data is obtained using a turbulent analogue of the Reynolds number calculated from the vortex viscosity of a turbulent medium.…”
mentioning
confidence: 99%